Free Odd Periodic Actions on the Solid Klein Bottle - Fawas M. Abudiak (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The cyclic actions of odd period and empty fixed point set are studied on the solid Klein Bottle K. It is shown that up to weak equivalence there is only one such action.